2015
DOI: 10.1371/journal.ppat.1004760
|View full text |Cite
|
Sign up to set email alerts
|

A Plasmodium Phospholipase Is Involved in Disruption of the Liver Stage Parasitophorous Vacuole Membrane

Abstract: The coordinated exit of intracellular pathogens from host cells is a process critical to the success and spread of an infection. While phospholipases have been shown to play important roles in bacteria host cell egress and virulence, their role in the release of intracellular eukaryotic parasites is largely unknown. We examined a malaria parasite protein with phospholipase activity and found it to be involved in hepatocyte egress. In hepatocytes, Plasmodium parasites are surrounded by a parasitophorous vacuole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 53 publications
1
119
2
1
Order By: Relevance
“…patic parasites (the mammalian form that multiplies in the liver (43,52)). PbPL-null sporozoites are impaired in their ability to pass through cell monolayers in vitro and to migrate through mammalian tissues to reach the liver, whereas PbLP-deficient liver forms have delayed release from liver cells, presumably due to a defect in PV membrane disruption.…”
Section: Discussionmentioning
confidence: 99%
“…patic parasites (the mammalian form that multiplies in the liver (43,52)). PbPL-null sporozoites are impaired in their ability to pass through cell monolayers in vitro and to migrate through mammalian tissues to reach the liver, whereas PbLP-deficient liver forms have delayed release from liver cells, presumably due to a defect in PV membrane disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Primary antibodies used for staining: monoclonal mouse anti- Pb HSP7042, rat anti- Pb MSP143, mouse anti- Pb EXP1; secondary antibodies: Alexa-Fluor® 488 goat anti-mouse IgG antibody, Alexa-Fluor® 546 goat anti-rat IgG antibody; DNA was revealed by Hoechst 33342 (all Life Technologies). Size measurements were carried out by acquisition of images with a Zeiss Axiovert 200 M microscope followed by analysis using Volocity (PerkinElmer).…”
Section: Methodsmentioning
confidence: 99%
“…The protein has a predicted signal peptide and its peak transcript expression was shown to be in the sporozoite stage. The orthologue of this enzyme in P. berghei, PbPL, was shown to support PVM rupture during parasite egress from the hepatocyte as discussed below (Burda et al, 2015). The PLA and membrane lytic activities of PbPL were demonstrated (Bhanot et al, 2005), potential acyltransferase activities have yet to be shown.…”
Section: Phospholipases Of Plasmodial Parasitesmentioning
confidence: 95%
“…a putative lecithin:cholesterol acyltransferase (LCAT; PFD37_0629300), which was demonstrated to be involved in membrane dynamics during hepatocyte invasion and egress by P. berghei parasites. This phospholipase, termed PbPL, exhibits membrane lytic activity in vitro and following hepatocyte infection, PbPL localizes to the PVM (Bhanot et al, 2005;Burda et al, 2015). Upon genetic knock-out, PbPL-deficient sporozoites lose their infectivity and their ability to cross epithelial cell layers.…”
Section: The Role Of Plasmodial Phospholipases During Life-cycle Progmentioning
confidence: 99%
See 1 more Smart Citation